Seleksi, Karakterisasi, Dan Reaktivitas Antibodi Monoklonal Virus Kerdil Kedelai : Selection, Characterization, And Reactivation Of Monoclonal Antibody On Soybean Stunt Virus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Abstract: Soybean Stunt Virus (SST) is a member ofCucumber mosaic virus group that caused soybean stunt disease. The disease is the most important viral disease ofsoybean in Indonesia. The objective of the study was to obtain SSV monoclonal antibody for detection SSV in both infected seed and plant Six hybridoma clones were obtained from fusion between spleen cells of BALB/c immunized with Soybean stunt virus and mouse myelome cell lines (NS-1)